3D Object Movement Transformation Using FPS and TPS Camera View Modes in OpenGL - MAULINA SAFITRI; RAMA YUSUF MAHENDRA; Rasyeedah Binti Mohd Othman; Riffani Fathia Annisa (Department of Electrical Engineering Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
Object transformation in three-dimensional space is a fundamental component in the development of interactive and realistic 3D modeling systems, particularly for control-based visual simulations and gaming applications. This study investigates the use of two camera viewpoint modes First-Person Shooter (FPS) and Third-Person Shooter (TPS) in a 3D object movement simulation implemented using OpenGL. The system is developed in Python using the Pygame library and applies basic object transformations, including translation, rotation, and scaling, based on homogeneous coordinates. Both camera modes are evaluated within the same simulation environment consisting of a car object, boundary walls, and obstacles. Experimental results show that the TPS camera mode provides better navigation performance by reducing collision frequency and offering a broader view of the environment, while the FPS camera mode delivers a more immersive experience with limited spatial visibility. Comparative graphs of navigation completion time and collision count highlight clear performance differences between the two camera modes. These results indicate that camera viewpoint selection significantly affects navigation efficiency and user experience in 3D visualization systems. The proposed simulation can serve as a foundation for visual-based control systems, virtual training environments, and educational applications involving spatial navigation.